INQUIRY - BASED SCIENCE EDUCATION IN DIGITIZED LEARNING ENVIRONMENTS - CALALB, Mihail (Acta et Commentationes, Sciences of Education, 2019)
The modern pedagogical context is characterised by the need for lifelong learning skills. The response to these challenges is given by constructivist pedagogy represented by Inquiry – Based Science Education. Three mandatory parts of educational process are emphasized: the constructivist pedagogy, two-way interaction between participants and digital technology. Digitalized learning environment doesn’t necessary mean only ICT tools and resources. The main conclusions are presented, such as: IBSE contributes to the formation of lifelong learning skills, interaction contributes to the building of active scientific vocabulary, and the digitalized learning environment requires digital and media literacy both for students and teachers